Ministry of Investment and Foreign Trade Decree No. 319 of the Year 2024 On the Conditions of Importing Cars for Personal Use = وزارة الاستثمار والتجارة الخارجية قرار رقم 319 لسنة 2024 بشأن شروط استيراد السيارات للاستعمال الشخصي - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic